The General in his Labyrinth: A 2D Video Game Adaptation for Cultural Education in Unity - Prieto-Patiño, Santiago Steven (2024)
This poster presents the development of an educational video game based on the novel “The General in his Labyrinth” by Gabriel García Márquez, focused on the context of e-learning applied to mobile environments. The objective of the project is to provide users with an interactive and attractive learning experience, taking advantage of the advantages that mobile devices offer in accessing information and learning. The initiative to turn the literary work into a video game could have educational advantages. The main goal is to promote literacy, attracting students who may not be interested in traditional reading. The interactive nature of the game has the potential to spark students’ curiosity about literature and motivate them to research the original book. In its 2D version, Unity allows you to create game environments and graphics in two dimensions, which is ideal for developing a game based on a literary work like this one. Unity makes it easy to incorporate elements of the story, characters, and literary world into an interactive game context thanks to its friendly interface and accessible development tools. It also seeks to promote cultural awareness around Simón Bolívar, who is a significant historical figure in Colombia. The video game, designed specifically for computers and mobile devices, combines the narrative power of an iconic novel with gamification elements. In this way, it seeks to promote interest in the literature and history of Colombia, while promoting cultural and civic values.